Mitochondrial Cholesterol in Alzheimer's Disease and Niemann–Pick Type C Disease - Torres, Sandra; García-Ruiz, Carmen M.; Fernandez-Checa, Jose C. (Frontiers in Neurology, 2019)
Mitochondrial dysfunction has been recognized as a key player in neurodegenerative diseases, including Alzheimer disease (AD) and Niemann-Pick type C (NPC) disease. While the pathogenesis of both diseases is different, disruption of intracellular cholesterol trafficking has emerged as a common feature of both AD and NPC disease. Nutritional or genetic mitochondrial cholesterol accumulation sensitizes neurons to A-mediated neurotoxicity in vitro and promotes cognitive decline in AD models. In addition to the primary accumulation of cholesterol and sphingolipids in lysosomes, NPC disease is also characterized by an increase in mitochondrial cholesterol levels in affected organs, predominantly in brain and liver. In both diseases, mitochondrial cholesterol accumulation disrupts membrane physical properties and restricts the transport of glutathione into mitochondrial matrix, thus impairing the mitochondrial antioxidant defence strategy. The underlying mechanisms leading to mitochondrial cholesterol accumulation in AD and NPC diseases are not fully understood. In the present manuscript, we discuss evidence for the potential role of StARD1 in promoting the trafficking of cholesterol to mitochondria in AD and NPC, whose upregulation involves an endoplasmic reticulum stress and a decrease in acid ceramidase expression, respectively. These findings imply that targeting StARD1 or boosting the mitochondrial antioxidant defence may emerge as a promising approach for both AD and NPC disease.